Interview with Lois Pinton (1) - Gwynne Langley and Toryn Miller-Stevens (Tufts Archival Research Center, 2006)
Interview conducted 2/25/05 at the Baptist Church, W. Springfield by Gwynne Langley and Toryn Miller-Stevens. Present were Lois Pinton, Toryn Miller-Stevens and Gwynne Langley.